Development of a multi-targeted real-time PCR assay for the detection of the grapevine pathogen Xylophilus ampelinus - Aleksander Benčič; Alexandra Bogožalec Košir; Janja Matičič; Manca Pirc; Neža Turnšek; Tanja Dreo (Plant Methods)
Abstract Background Xylophilus ampelinus is a plant pathogenic bacterium that causes bacterial blight in grapevines, which can lead to severe yield losses and economic damage. Owing to its fastidious growth on culture media, detection is primarily based on molecular methods. However, existing tests have produced inconsistent results, particularly when used to detect latent infections and non-validated matrices. There is a risk of false-positive results, with economic consequences such as restrictions on international trade. To enhance the diagnostics of X. ampelinus, a genome-informed approach was utilised to identify new potential targets for specific detection. On the basis of these sequences, multiple real-time PCR assays were designed, and their specificity and sensitivity were assessed, as well as their performance validated across three different grapevine tissues, including leaves, roots, and xylem. Results The newly designed real-time PCR assays were evaluated via high throughput testing for specificity and sensitivity and compared with a reference assay. The most promising assays were selected and validated in different grapevine tissues and included in a test performance study to validate their reproducibility and robustness. Three new assays (Xamp_BA_2, TXmp22.4, and Xamp_BA_7) demonstrated high specificity and sensitivity for X. ampelinus detection. The Xamp_BA_2 assay exhibited the best overall performance, offering high diagnostic sensitivity and robustness across diverse plant matrices. Importantly, the assays exhibited no cross-reactivity with non-target bacterial species and maintained high detection accuracy across diverse grapevine tissue types. Conclusions The newly developed real-time PCR assays provide an enhanced diagnostic framework for the detection of X. ampelinus in various plant matrices, significantly improving the applicability of molecular testing. The Xamp_BA_2 assay demonstrates superior performance and is recommended for routine diagnostics, with other validated assays being employed for confirmation of identification. The development of these new assays represents a significant expansion of our toolkit for the precise detection of X. ampelinus in grapevines, with the potential to contribute to the mitigation of grapevine bacterial blight, the prevention of yield losses, and the protection of international trade in grapevine material. Further implementation of these assays will support regulatory and phytosanitary efforts to mitigate the spread of X. ampelinus.